Integration of Artificial Intelligence (AI) in Islamic Religious Education Learning: Opportunities and Challenges in the Digital Era - Yeni Yuliana (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: Islamic Religious Education (PAI) is not merely a medium for transferring theoretical religious knowledge, but a sacred instrument oriented toward the development of students' personality, morals, and religious character. However, technological acceleration in the digital era triggers a double disruption through the emergence of the Artificial Intelligence (AI) ecosystem, which brings massive shifts in learning patterns characterized by a preference for an instant culture and a high dependency on cyber data. This study aims to comprehensively analyze the pedagogical opportunities as well as the ethical-moral challenges in integrating Artificial Intelligence (AI) into PAI learning.Method: This research utilizes a descriptive qualitative approach to unravel the phenomena holistically and contextually in the field. Research informants were determined through purposive sampling and snowball sampling techniques. The data collection procedure relies on three main techniques: participant observation of digital classroom dynamics, in-depth interviews with PAI teachers and students, and academic documentation. Data validity was verified through methodological triangulation and a thorough examination of the final report. Data analysis was processed through the stages of data reduction, data presentation, and conclusion drawing.Result: The results indicate that the integration of AI in PAI opens substantial opportunities for material personalization, adaptive learning, the transformation of interactive instructional media, and the efficiency of independent evaluation through voice recognition applications for Quranic makhraj correction. Nevertheless, this integration triggers serious challenges in the form of the risk of reducing the teacher's dimension of Uswatun Hasanah or spiritual role-modeling, a potential academic integrity crisis due to an instant mentality of relying on machine answers, and the threat of validity bias regarding religious content on the internet.Conclusion: This study concludes that AI must be wisely positioned as a supplementary tool (wasilah), while the PAI teacher remains an irreplaceable main pillar (ghayah) in safeguarding the morality and spirituality of students in the digital era.